KONTRIBUSI TENAGA KERJA DALAM KELUARGA TERHADAP PENDAPATAN USAHATANI PADI (Oryza sativa L) DI DESA TAMBAK SIRANG LAUT KECAMATAN GAMBUT KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Bahrun Bahrun (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
This research intent to know technical aspect and farmings economic aspect paddy, and to know labour contribution in family to farming income paddy at Tambak Sirang Laut   Village.  Pull samples by use of survey method with tech observation, farmer sampling that perform paddy farming which is by use of simple random tech( Simple random is sampling ).   Total farmer that labour varietas's paddy farming Unus's Siam as much 80 person,  then done by take at random simple( Simple Random is Sampling ) as much 36 % (30 person) of all population.  Paddy production average 2.135,00 kg / farmer or as big as 4.270,00 kg / ha (4,3 tons / ha).  Acceptance average as big as Rp. 19. 215. 000,00 / farmer or Rp. 38. 430. 000,00 / ha On A Par income as big as Rp. 16. 805. 103,78 / farmers or as big as Rp. 33. 610. 207,57 / ha labour Percentage in family (TKDK) to full scale labour (TK) which is as big as 48,02%. labouring contribution in family to paddy farmer income average as big as 10,29%.